Orally administered recombinant Lactobacillus expressing African swine fever virus antigens that induced immunity responses - Zhang, Hongliang; Zhao, Saisai; Zhang, Haojie; Shen, Yu; Zhang, Peijun; Shan, Hu; Cai, Xiulei (Frontiers in Microbiology, 2023)
African swine fever (ASF) is a highly contagious, acute, febrile disease caused by the African swine fever virus (ASFV), with morbidity and mortality rates approaching 100% in domestic and wild swine, resulting in massive economic losses to the pig industry worldwide. This study aimed to express the p30, p54, and p72 proteins encoded by ASFV in vitro using the Lactobacillus lactis (L. lactis) expression system. Here, six new functional recombinant L. lactis were constructed, and the expression of the p30 protein, p54 protein, p72 protein, p30-LTB fusion protein, p54-LTB fusion protein, and the p72-LTB fusion protein was successfully detected by Western blot analysis. Following oral immunization of rabbits with recombinant L. lactis, serum IgG, intestinal mucosal sIgA, cytokines (IL-4 and INF-γ), and splenocyte viability were higher than in the control group via ELISA. Notably, without the LTB adjuvant group, humoral and Th1 cellular immunity were promoted, whereas, with the LTB adjuvant group, local mucosal immunity, humoral immunity, and Th2 cellular immunity were promoted, providing new insights into the design and development of an ASFV subunit vaccine.